2003
DOI: 10.1088/0305-4470/36/25/320
|View full text |Cite
|
Sign up to set email alerts
|

Ghost condensates and dynamical breaking ofSL(2,R) in Yang–Mills in the maximal Abelian gauge

Abstract: Ghost condensates of dimension two in SU (N ) Yang-Mills theory quantized in the Maximal Abelian Gauge are discussed. These condensates turn out to be related to the dynamical breaking of the SL(2, R) symmetry present in this gauge.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Significantly, similar identities for the analogous operator exist in other gauges such as the maximal abelian gauge (MAG), [15,16], and in space-time dimensions other than four, [17]. Since these dimension two operators have been the subject of intense analytic investigation in various gauges in recent years, see, for instance [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] and references therein, due to their condensation in a non-trivial vacuum, there is a clear need to renormalize QCD in this gauge. In particular the explicit values of all the anomalous dimensions are required as the first step in the extension of the local composite operator (LCO) method for QCD, [18], to the MAG in various colour groups.…”
Section: Introductionmentioning
confidence: 94%
“…Significantly, similar identities for the analogous operator exist in other gauges such as the maximal abelian gauge (MAG), [15,16], and in space-time dimensions other than four, [17]. Since these dimension two operators have been the subject of intense analytic investigation in various gauges in recent years, see, for instance [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32] and references therein, due to their condensation in a non-trivial vacuum, there is a clear need to renormalize QCD in this gauge. In particular the explicit values of all the anomalous dimensions are required as the first step in the extension of the local composite operator (LCO) method for QCD, [18], to the MAG in various colour groups.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, (gauge-dependent) condensates of mass di-mension two have also received considerable attention [29,[70][71][72][73][74][75][76][77][78][79][80][81][82]. In particular, the gauge condensate A b µ A b µ has been largely studied, since it should be sensitive to topological structures such as monopoles [70] and it could play an important role in the quark-confinement scenario through monopole condensation [83].…”
Section: Figmentioning
confidence: 99%
“…These condensates were first introduced in SU (2) gauge theory in maximally Abelian gauge (MAG) [7,10,27,32,39,40,41]. More recently, the same condensates have been studied in other gauges [6,8,9,13,28,30], such as the CurciFerrari and the Landau gauges.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases it was found that the ghost condensates are related to the breakdown of a global SL(2, R) symmetry [6,42]. In MAG the diagonal and off-diagonal components of the ghost propagators are modified [7,27] by ghost condensation. Similar results have been obtained in other gauges [13,30].…”
Section: Introductionmentioning
confidence: 99%